(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2026)
A polyelectrolyte system based on carboxymethyl cellulose (CMC) and water-soluble chitosan was developed and evaluated as wet and dry strength agent for paper. Chitosan was chemically modified through carboxymethylation to produce water-soluble carboxymethyl chitosan (CMCh), confirmed by FTIR analysis with characteristic peaks at 1586 cm⁻¹ and 1400 cm⁻¹. CMCh exhibited enhanced water solubility, particularly at elevated temperatures, and demonstrated improved conductivity, making it suitable for applications such as polyelectrolytes. In papermaking, CMCh, carboxymethyl cellulose (CMC), and their combination significantly improved dry and wet strength properties, including tensile, tear, and burst indices, with a synergistic effect observed in their combined use. The dry and wet tensile index of refined pulp increased from 55.48 N.m/g to 66.67 N.m/g and 2.48 N.m/g to 4.1 N.m/g, respectively, with the addition of 1.0% CMCh. CMCh also enhanced filler retention, increasing ash content from 3.6% to 6.89%. These findings highlight CMCh as a versatile additive for improving paper strength and filler retention. Bangladesh J. Sci. Ind. Res. 61(1), 1-8, 2026